2013
DOI: 10.1016/j.drugalcdep.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and drug use among young adults driving to a drinking location

Abstract: Background Clubs that feature electronic music dance events (EMDEs) draw young adults aged 18 to 34 who are at high-risk for alcohol-related crashes to locations where alcohol sales are the principal source of revenue. Up to 30% of these attendees may also use drugs. This provides an important context in which to study driving arrangements that reflect concern with impaired driving. We explored whether drivers were using less alcohol and fewer drugs at exit than their passengers were and whether a driver for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…This provides the opportunity to collect objective measures of substance use at both entry and exit: breath samples (to test for alcohol) and oral fluid samples (to test for drugs). The Pacific Institute for Research and Evaluation (PIRE) has conducted portal survey studies at the border crossing into Tijuana, Mexico (Johnson, 2012;Johnson & Clapp, 2011;Kelley-Baker et al, 2012;Lange et al, 2006aLange et al, , 2006b, and at the entrances to clubs that feature electronic music (e.g., Johnson et al, 2012;Miller et al, 2005Miller et al, , 2009Miller et al, , 2013aVoas et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides the opportunity to collect objective measures of substance use at both entry and exit: breath samples (to test for alcohol) and oral fluid samples (to test for drugs). The Pacific Institute for Research and Evaluation (PIRE) has conducted portal survey studies at the border crossing into Tijuana, Mexico (Johnson, 2012;Johnson & Clapp, 2011;Kelley-Baker et al, 2012;Lange et al, 2006aLange et al, , 2006b, and at the entrances to clubs that feature electronic music (e.g., Johnson et al, 2012;Miller et al, 2005Miller et al, , 2009Miller et al, , 2013aVoas et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Although hosted in legitimate, regulated establishments and part of normal entertainment for diverse patrons, EMDE environments often are the scene of negative behaviors like drinking and driving or riding with an impaired driver Voas et al, 2013) and sexual and physical aggression (Miller et al, 2015). Data from ongoing research show that EMDE patrons are wary about the risks associated with the clubs they attend, with more than 60% reporting at least some concern for their safety.…”
mentioning
confidence: 99%
“…Moreover, it should be noted that drink driving seems to be associated with the non-usage of vehicle safety devices such as seat-belts or crash helmets in the case of motorcyclists (Bergen et al, 2011;Woratanarat et al, 2009). Despite this, Voas et al (2013) found evidence of some precautionary behavior amongst youngsters when leaving a drinking location.…”
Section: Literature Reviewmentioning
confidence: 43%
“…Moreover, it should be noted that drink driving seems to be associated with the non-usage of vehicle safety devices such as seat-belts or crash helmets in the case of motorcyclists (Bergen et al, 2011;Woratanarat et al, 2009). Despite this, Voas et al (2013) found evidence of some precautionary behavior amongst youngsters when leaving a drinking location.…”
Section: Literature Reviewmentioning
confidence: 77%
“…Voas et al (2013) point out that drivers with a high BAC level switched to passenger status and were replaced by former passengers with lower levels as a means to avoid alcohol-impaired driving.…”
Section: Literature Reviewmentioning
confidence: 99%